Diphenyl Diselenide Catalyzed Oxidative Degradation of Benzoin to Benzoic Acid - Cao, Hongen; Chen, Tian; Yang, Chenggen; Ye, Jianqing; Zhang, Xu (Synlett, 2019)
The diphenyl diselenide catalyzed oxidative degradation of benzoin to benzoic acid is reported. As this reaction can convert the malodorous compound into an odorless and innocuous product under mild conditions, it might be useful for pollutant disposal. The reaction does not require a transition-metal catalyst or a chemical oxidant, so that it can be performed at low cost and without generation of wastes. This is believed to be the first example of the use of organoselenium catalysis technology in pollutant destruction, thereby expanding its range of applications.
Keywords: diphenyl diselenide; organoselenium catalysis; green chemistry; benzoin; pollutant destruction; benzoin